Analisis Kapasitas Penampang Sungai untuk Mengidentifikasi Banjir Menggunakan Software HEC-RAS 6.3.1 - Ahmad Fajrin; Asrul; Nurnawaty; Indriyanti (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
Floods occur due to a situation where the water flow is not accommodated Banjir, Hec-ras 6.3.1, Sungai. by the riverbed, as a result floods can cause property losses and loss of life. The purpose of this study was to determine the capacity of the Pangkajene River cross-section and identify flood overflows that occurred in the Pangkajene River. The model used in this study is the flow Hec-ras 6.3.1 (River Analysis System (RAS) Center (HEC). The results of the study showed that many river cross-section points experienced overflows and the highest discharge point was at STA 2400 of 254.48 m3/sec and an overflow height of 1.0 m. The main cause is the high intensity of rainfall accompanied by sedimentation deposits in the river which makes the river shallower so that almost every year there is a flood overflow at the research location